Legal and Illegal Drug Consumption among Students at the University of Seville (Spain) - Vicente Llorent-Bedmar; Lucía Torres-Zaragoza; Susana Vidigal-Alfaya (MDPI AG, 2023)
In current society, the fight against drug abuse is an important social challenge given its harmful effects on health and quality of life, globally. Numerous studies show that university life fosters drug use among university students. This research explores the perceptions of legal and illegal drug use of undergraduate students at the University of Seville (Spain). The research design is quantitative: a specific questionnaire was administered to a sample of 1478 students. Descriptive and inferential statistics were used for data analysis using SPSS v.27 software. It is found that the majority of students do not use illegal drugs, although they do use alcohol and tobacco. Students with a failing grade average use more legal and illegal drugs than those who have outstanding grade averages. There are gender differences in drug use, with males using legal and illegal drugs more than females. Nevertheless, women report taking more tranquillizers and sleeping pills. It is necessary for universities to develop policies for the prevention of legal and illegal drug use, as well as the creation of training programs and counselling courses to promote good health.